Ansiedad y Habilidades Sociales en los estudiantes de educación básica de la unidad educativa “Once de Noviembre”, Riobamba, octubre 2017 – marzo 2018. - Parra Jiménez, Stalin Vinicio (2018)
The objective of this research was to determine the relationship between anxiety and its incidence in the development of social skills in students of the tenth year of Basic Education "A and B" of the Educational Unit Eleven of November, academic period October 2017- March 2018, given that anxiety is an emotional state that causes different manifestations, affecting the social skills of students, which is related to social behavior in its multiple manifestations, the methodology used to carry out this research had a qualitative approach with a non-experimental design, with an exploratory level, with a type of bibliographic and field study, the population was the students of the Educational Unit "Once de Noviembre", the sample was not probabilistic and intentional and it was worked with 60 students, the techniques that were applied were GADI Psychometric Test and the Test of Skill Social, the instruments were the GADI anxiety scale and the Goldstein Social Skills Scale, where it was evidenced that anxiety could be analyzed if it has a significant relationship with social skills, when a person has phobias, fears, tachycardias, they sweat their hands, they are unable to relate to other people, since many of the times they have scenes of panic that they can not talk about.